Educational Tourism Potential for Sustainable Tourism - Aziizah Nurul Fadhiilah Djalle; Andi Bahri Soi; Adhitia Pahlawan Putra (Universitas Merdeka Malang, 2024)
Sustainable tourism is defined as tourism development that meets the needs of tourists while maintaining environmental sustainability and benefiting current and future generations. In an effort to support sustainable tourism in Parepare City, this research identifies the potential for educational tourism by exploring and explaining the potential for educational tourism that can be developed to support sustainable tourism. The city of Parepare has 3 destinations that have the potential to support educational tourism activities, namely the Jompie Botanical Gardens, the BJ Habibie Museum and the BRIN Earth Station Field Station Area. Data collection techniques come from primary data sources obtained directly through interviews and direct observation. Secondary data was obtained by reading literature studies such as journals, articles and the internet. At the research location, a series of intensive observations were also carried out regarding the characteristics of tourist destinations, namely attractions, accessibility, amenities, with managers directly. The selected informants include visitor managers and parties related to the research location. Interviews were conducted to obtain further information about possible educational tourism efforts to support sustainable tourism. The results achieved in this research show that the Jompie Botanical Gardens, the BJ. Habibie Museum, and government research institutions such as the BRIN Earth Station Field Station Area have programs and activities that can develop educational tourism potential in Parepare City.